Comprehensive analysis of VEGF/VEGFR inhibitor-induced immune-mediated hypertension: integrating pharmacovigilance, clinical data, and preclinical models - Kuang, Hongyu; Yan, Qingkai; Li, Zhanzhi; Lin, Anqi; Li, Kailai; Zhang, Jian; Luo, Peng; Yin, Yuehui (Frontiers in Immunology, 2024)
This study aimed to elucidate the differential immunological mechanisms and characteristics of hypertension induced by VEGF inhibitors (VEGFi) and VEGF receptor inhibitors (VEGFRi), with the goal of optimizing monitoring strategies and treatment protocols. We investigated the risk of immune-related adverse events associated with VEGFi/VEGFRi-induced hypertension by analyzing the FDA Adverse Event Reporting System (FAERS) database, corroborating findings with blood pressure characteristics observed in clinical patients and preclinical models exposed to various VEGF/VEGFRi. Analysis of FAERS data, in conjunction with clinical observations, revealed that both VEGFi and VEGFRi significantly elevated the risk of immune-mediated, blood pressure-related adverse events (ROR=7.75, 95% CI: 7.76-7.95). Subsequent clinical and preclinical studies demonstrated differential immunological responses and hypertension profiles between inhibitor classes. VEGFRi exhibited a more rapid onset, greater blood pressure elevation, and higher incidence of immune-mediated adverse events compared to VEGFi (Systolic BP: ROR=0 for VEGFi vs. ROR=12.25, 95% CI: 6.54-22.96 for VEGFRi; Diastolic BP: ROR=5.09, 95% CI: 0.60-43.61 for VEGFi vs. ROR=12.90, 95% CI: 3.73-44.55 for VEGFRi). Integrative analysis across cancer types and species, focusing on key signaling pathways, revealed that VEGF/VEGFRi-induced blood pressure elevation was associated with immunomodulation of the mitogen activated protein kinase (MAPK) pathway (R=-0.379, P=0.0435), alterations in triglyceride metabolism (R=-0.664, P=0.0001), modulation of myo-inositol 1,4,5-trisphosphate-sensitive calcium release channel activity (R=0.389, P=0.0378), and dysregulation of nitric oxide eNOS activation and metabolism (R=-0.439, P=0.0179). Both VEGFi and VEGFRi significantly augmented the risk of immune-mediated, blood pressure-related adverse events, with the temporal dynamics of these effects demonstrating greater significance than dose-dependent responses. VEGFRi induced a more rapid and pronounced onset of blood pressure elevation, accompanied by a higher incidence of immune-related, blood pressure-associated adverse events, compared to VEGFi.